2013
DOI: 10.3174/ajnr.a3706
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Change in Apparent Diffusion Coefficient as an Imaging Biomarker for Predicting Treatment Response in Head and Neck Cancer Treated with Chemoradiotherapy

Abstract: BACKGROUND AND PURPOSE: ADC provides a measure of water molecule diffusion in tissue. The aim of this study was to evaluate whether the fractional change in ADC during therapy can be used as a valid predictive indicator of treatment response in head and neck squamous cell carcinoma treated with chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 25 publications
2
69
1
Order By: Relevance
“…DW MRI studies, in the context of chemoradiotherapy alone, have demonstrated an increase in ADC in responders and a lower increase or decrease 1-3 wk into radiotherapy in nonresponders (13,26,27). Although our DW MRI data with IC showed similar trends, it was unable to distinguish eventual responders from nonresponders.…”
Section: Discussioncontrasting
confidence: 53%
“…DW MRI studies, in the context of chemoradiotherapy alone, have demonstrated an increase in ADC in responders and a lower increase or decrease 1-3 wk into radiotherapy in nonresponders (13,26,27). Although our DW MRI data with IC showed similar trends, it was unable to distinguish eventual responders from nonresponders.…”
Section: Discussioncontrasting
confidence: 53%
“…Overall, there were conflicting results over the value of pre-treatment ADC at predicting response to treatment (Table 1). Five studies failed to distinguish patients with unfavourable disease based on pretreatment ADC, [35][36][37][38][39] whereas six studies found high pretreatment tumour ADC to be predictive of poor outcome following RT. [40][41][42][43][44][45] As illustrated in Table 1, there are heterogeneities between the studies in scanning protocol, analytical methods and measured clinical end points, which may be Figure 3.…”
Section: Functional Mri Sequencesmentioning
confidence: 98%
“…36,37,40,49 The cumulative results suggest that tumours that show a lower increase or even a decrease in ADC 1-4 weeks into radiotherapy (ΔADC ,14-24%) are more likely to fail treatment. It is speculated that tumours with a good treatment response show a higher frequency of apoptosis or necrosis earlier in the course of treatment than those with a poor response.…”
Section: Functional Mri Sequencesmentioning
confidence: 99%
“…The ADC increase within/ after the treatment of complete responders is also significant when compared to the pre-treatment ADC, while nonresponders are more associated with a lower increase or even a decrease of ADC during the treatment (28,(31)(32)(33)(34)(35). In addition, The ADC change might be a more sensitive and accurate biomarker to predict locoregional control (LRC) than the volume change of tumors (36).…”
Section: Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%